Európsky hodokvas - Lukáč, Emil Boleslav; Kraus, Milan; Salamon, Zoltán (Bratislava Slovenský spisovateľ, 1971)
oloch; Bábel; Stĺp hanby; Óda na poslednú a prvú; Parížske romance
Keywords: Poézia; Povinná lit